The Effect of Arm Muscle Strength on Overhand Service Performance in Volleyball Extracurricular Activities at SMPN 01 Koto Baru - Dian Estu Prasetyo; maldin ahmad burhan; Jea Henita (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the effect of arm muscle strength on overhand serve performance among volleyball extracurricular players at SMPN 01 Koto Baru. This research employed an experimental method with a sample of 17 selected volleyball players. Arm muscle strength was measured using a push-up test, while overhand serve performance was assessed using an overhand serve test. The results indicate a significant effect of arm muscle strength on overhand serving performance. The stronger the arm muscles, the better the overhand serve results. This study concludes that arm muscle strength is an important factor in improving overhand serve ability in volleyball players.